Four-Dimensional XStrain Echocardiographic Assessment of Left Ventricular Strain and Rotational Mechanics: Technology, Clinical Applications, Advantages and Limitations - Akhil Mehrotra; Anurag Mehrotra; Mohammed Shaban; Shubham Kacker (Cardiovascular Innovations and Applications)
Because of its excellent ability to non-invasively assess left ventricular (LV) systolic function, two-dimensional speckle tracking echocardiography (STE) is increasingly being used in echocardiographic laboratories worldwide. Two-dimensional STE is the most sought-after method to evaluate LV strain, rotation, twist and torsion. Two dimensional, three-dimensional and four-dimensional (4D) deformation estimation by STE has several intrinsic limitations. For better appraisal of LV contractile properties, a recently introduced updated version of 4D XStrain STE has been used to analyse the various complex multidimensional LV mechanics. This novel technology is a reliable, economical and simple tool for estimating regional and global myocardial function. Furthermore, 4D XStrain STE can accurately quantify the 4D LV ejection-fraction, LV volume and sphericity index. However, this technology has not been extensively implemented, and its assessment remains limited primarily to research applications. Hence, we aim to promote this innovative technology by comprehensively addressing its technique, advantages and limitations, so that it can be better applied in cardiovascular disease.